Analisis Penyajian Iklan Di Media Online Tribun Sumsel.Com - Rubim Jaya Kusuma; Sumaina Duku; Ahmad Harun Yahya (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2023)
Marketing has evolved into a more nuanced and distinctive form of communication in the modern era due to advances in technology. The integration of communications and marketing is an important component in capturing customer attention. Specifically, this study looks at how digital advertising is presented using a qualitative research approach, which is a scientific method. In qualitative research, researchers use real-world settings to spark new ideas. Qualitative research relies heavily on the researcher. Therefore, to conduct a thorough analysis of the object being studied, researchers need access to a wealth of theories and insights. The advertising presentation method is the main focus of this research. Two types of data, primary and secondary, were used to construct this research. Interviews and media news presentation surveys on Tribun Sumsel.com provide the main data used in this research. Articles, books, journals, and websites serve as secondary sources for this research data. There is a clear purpose and meaning to conducting an interview that goes beyond random conversation. Achieve dominance in the Sumatra online media market and become a leading newspaper publishing company. Share reliable information to inspire new thought patterns and promote the establishment of democracy in Sumatra. Maintain an honest, productive and profitable company. Gojek advertising media on Tribun Sumsel.com displays signs, objects and interpretants, as determined by semiotic analysis. Gojek is a transportation reservation app, and the second image shows a food reservation. This can be seen from the technique of taking images, colors and advertising text, which includes signs such as vehicles and drivers carrying passengers. Everything from the placement of the image to the expressions and words written on it conveys the verbal and nonverbal messages in this advertisement.